2010
DOI: 10.1097/tp.0b013e3182000027
|View full text |Cite
|
Sign up to set email alerts
|

Customized Mycophenolate Dosing Based on Measuring Inosine-Monophosphate Dehydrogenase Activity Significantly Improves Patients' Outcomes After Renal Transplantation

Abstract: The data suggest that measuring biologic response may be a more valuable indicator than traditional therapeutic drug monitoring of MPA. Patients at risk for rejection could be earlier identified, and the therapeutic potential of MPA will be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
15
0
6
Order By: Relevance
“…This study has the limitation of a small patient number, so large-scale prospective studies are needed to substantiate our results and to determine the optimal GVHD prophylaxis regimen. Moreover, measuring the levels of the unbound form of MPA 11 or the activity of inosine monophosphate dehydrogenase isoenzymes 12 may be necessary to analyze the direct effects of MMF on lymphocytes after CBT. Abbreviations: CNI = calcineurin inhibitor; MAC = myeloablative conditioning; MMF = mycophenolate mofetil; N = no; NCC = nuclear cell count; RIC = reducedintensity conditioning; Y = yes.…”
mentioning
confidence: 99%
“…This study has the limitation of a small patient number, so large-scale prospective studies are needed to substantiate our results and to determine the optimal GVHD prophylaxis regimen. Moreover, measuring the levels of the unbound form of MPA 11 or the activity of inosine monophosphate dehydrogenase isoenzymes 12 may be necessary to analyze the direct effects of MMF on lymphocytes after CBT. Abbreviations: CNI = calcineurin inhibitor; MAC = myeloablative conditioning; MMF = mycophenolate mofetil; N = no; NCC = nuclear cell count; RIC = reducedintensity conditioning; Y = yes.…”
mentioning
confidence: 99%
“…25 In previous studies, the activity of IMPDH in lymphocytes has been used as a pharmacodynamic biomarker for MPA. [4][5][6][7][8][9]26,27 Our reported LC-MS/MS assay has a short run time, and it can be used to study IMPDH activity and also purine bases that are closely related to the biochemical function of this enzyme. In addition to measurement of the direct inhibitory effect on IMPDH that is mediated by an inhibitor like MPA, the molecular consequences of targeting IMPDH may also be determined with the assay.…”
Section: Discussionmentioning
confidence: 98%
“…Quantification of IMPDH activity in circulating blood lymphocytes has demonstrated potential as a useful biomarker for the pharmacological response to MPA. [4][5][6][7][8][9] Yet, the exact application of IMPDH as pharmacodynamic biomarker in transplant recipients using MPA has to be determined in clinical studies. A complementary approach may be to explore the levels of free purine nucleotides in parallel with the IMPDH activity in lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…In an outcome study, IMPDH activity was measured as the area under the enzyme curve over the first 4 hours after dose administration in renal transplant recipients treated with enteric coated mycophenolate sodium (EC-MPS) [17]. It was demonstrated that IMPDH inhibition was significantly lower in patients with rejection compared to patients with no rejection during the first and second weeks after transplantation.…”
Section: Drug Target Enzymesmentioning
confidence: 99%